Studi Hermeneutik-Filosofis Teks Lelaku Tapa Wuda Ratu Kalinyamat sebagai Simbol Pendidikan Agama Islam - Muhammad Rifqi Zam Zami; Nur Widad Mazaya; Widia Astuti (Transformasi Manageria: Journal of Islamic Education Management, 2024)
This article discusses about the hidden meaning of tapa wuda that had performed by Kalinyamat Queen as a symbol of Islamic education. This ritualistic behavior recorded in the Babad Tanah Jawi text which is often invites controversy about its meanings. Many people interpret tapa wuda textually as "asceticism without wearing clothes". Scientific studies with a hermenautic approach will reveal what means in this fragment of the Babad Tanah Jawi text. The method that is used in this journal is a descriptive qualitative method which will present data and findings in the form of descriptive writing. The results show that tapa wuda is a symbol that has meanings of the importance of an educational environment, patience, asceticism, and strong determination and purpose in seeking knowledge to gain wisdom in thinking and acting. Keywords: Tapa Wuda, Kalinyamat Queen, Hermenautic.